2015
DOI: 10.1002/asia.201500555
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Chemistry in Microflow Fields: Toward a New Material World of Precise Kinetic Control

Abstract: Constructing new and versatile self-assembling systems in supramolecular chemistry is much like the development of new reactions or new catalysts in synthetic organic chemistry. As one such new technology, conventional supramolecular assembly systems have been combined with microflow techniques to control intermolecular or interpolymer interactions through precise regulation of a flowing self-assembly field. The potential of the microflow system has been explored by using various simple model compounds. Unifor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 97 publications
1
23
0
Order By: Relevance
“…, the concentration gradients and solvent composition in space, and the interfaces at which nucleation occurs. Numata and co-workers 39 used microfluidic conditions for the kinetically controlled preparation of porphyrin assemblies from nano to micro scale. For example, they found that the polymerization of H 2 TPPS to form J-aggregates, as triggered by its protonation, is strongly enhanced under microfluidic mixing, and occurs at final conditions at which it is not observed in a flask ( Fig.…”
Section: Methods To Reach Non-dissipative Non-equilibrium States (#2mentioning
confidence: 99%
“…, the concentration gradients and solvent composition in space, and the interfaces at which nucleation occurs. Numata and co-workers 39 used microfluidic conditions for the kinetically controlled preparation of porphyrin assemblies from nano to micro scale. For example, they found that the polymerization of H 2 TPPS to form J-aggregates, as triggered by its protonation, is strongly enhanced under microfluidic mixing, and occurs at final conditions at which it is not observed in a flask ( Fig.…”
Section: Methods To Reach Non-dissipative Non-equilibrium States (#2mentioning
confidence: 99%
“…Applying well-controlled external triggers should bring interesting self-assembling effects and may result in new kinds of self-assembled materials with more controlled properties. Some studies described the use of shear stress, 26,[29][30][31][32][33] controlled reagent exchanges in microfluidic devices, [34][35][36][37][38] electrical 39 or magnetic fields, 40,41 surface effects [42][43][44] or ice growth 45 to control self-assembly. While microfluidics is often used to control the self-assembly of micelles, particles, liquid crystals and some polymers, 46,47 it is scarcely the case for molecular gels.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to this general behavior in solution, we have found that the efficiency of J-aggregate formation is correlated to the time required for protonation of H 4 TPPS [1]. Very rapid proton diffusion in a microflow channel [9][10][11][12][13][14] results in increasing temporal H 4 TPPS concentrations, even at a constant value of pH [15,16].…”
Section: Introductionmentioning
confidence: 56%